(untitled) (FAVE Sección Ciencias Veterinarias, 2021)
Anaplasma platys is a Gram-negative, intracellular obligate bacterium that is transmitted by Rhipicephalus sanguineus ticks and has been identified in most of the country. It is the causative agent of canine infectious cyclic thrombocytopenia. The objective of this work is to report the finding of morulae compatible with A. platys in the blood smear of a 10-year-old male Weimaraner canine who was treated at the Hospital de Salud Animal of the Facultad de Ciencias Veterinarias of the Universidad Nacional del Litoral, in the city of Esperanza. The case could not be followed up, because the patient died a few days after his first consultation. The detection of obligate intracellular pathogens in blood smears has low sensitivity and specificity, therefore confirmation of the causative agent must be performed using PCR. Due to the severity of the condition presented in this case, it is necessary to differentiate the presence of Ehrliquia canis and confirm the finding of A. platys using PCR. Current scientific evidence reveals that the zoonotic potential of A. platys is very low or nil.